Development and Application of a Web-based Integrated Support Service Program for Infertile Women. - Park, Jummi; Shin, Nayeon (Inquiry (00469580), 2021)
Online-based infertility education provides a health management system to patients using electronic information and technology and no face-to-face interaction with patients and experts. This is a study to develop a web-based integrated support service system to meet the health care and nursing needs of infertile women. To develop a system that is most suitable and practically helpful to infertile women, who are end users of this system, research was conducted. This education system consists of introduction to women's health care, information on women's health, information on organizations for women, community for infertile women, and request for consultation for health management and nursing education of infertile women. This study introduced and applied a user-centered design that maximizes the value of use by first understanding the user's convenience and needs when developing a program.